FREQUENCY OF HOSPITAL ACQUIRED HYPONATREMIA IN A PEDIATRIC TERTIARY CARE SETTING - Bibi, Shawana; Bibi, Saima; Gilani, Syed Yasir Hussain; Shah, Syed Raza Ali; Haq, Anwar ul; Billo, Abdul Ghaffar (Journal of Ayub Medical College Abbottabad, 2015)
Background: Hyponatremia is the most commonly encountered electrolyte disorder in children. In our country the epidemiology of hospital acquired hyponatremia has hardly ever been explored whereas the administration of hypotonic IV fluids is widely practiced here. Therefore we pioneered to conduct this study to determine the frequency of hospital acquired hyponatremia. Methods: This was a cross sectional study carried out at Aga Khan University Hospital, Karachi in paediatric ward and ICU over a period of 12 months. All children (>1 month and <15 years of age ) admitted in paediatric units and on maintenance IV fluids who had serum sodium level measured on admission ,were included in the study and followed to identify patients who had a drop in serum sodium during hospitalization. Informed consent was taken from parents and collected data was recorded on a pro forma. Results: A total of 865 patients were enrolled in the study. Hyponatremia was recorded in 405 patients on admission (46.8%) while hospital acquired hyponatremia was documented in 240 children (27.7%). Out of these 142 (59.2%) were male and 98 (40.8%) were female. Mean age of children in hospital acquired hyponatremia group was 60.67 months. Severity of hospital acquired hyponatremia was recorded as mild in 191 (79.6%), moderate in 35 (14.6%) and severe in 14 (5.8%) children. Major disease categories included gastrointestinal disorder (30.4 %), respiratory illness (12.5%), oncological disease (16.3%), cardiovascular disease (11.7%), infectious disease (9.2%) and neurological illness (8.3%). Conclusion: Hospital acquired hyponatremia is frequently encountered in our hospitalized children with majority of them receiving hypotonic IV solutions.